Direct martensitic transformations of low-carbon steels - Belykh, D.G.; Skoromna, S.F.; Tkachenko, V.I. (Problems of Atomic Science and Technology, 2023)
The proposed model is based on the use of the principle of detailed equilibrium, which occurs during phase transitions of the crystal lattice. This theory complements the theory of Landau phase transitions in crystalline media, as well as the theory of crystallization of matter by Kolmogorov and Avrami. In the proposed theory, martensitic transformations are described by equations of induced transitions between two energy levels, which correspond to the number of particles of the original phase with low energy (austenite) and the number of particles of the transformed phase with higher energy (martensite). The source of transformations are particles of the third kind – phonons, the number of which is related to the induced transitions of particles between energy levels and depends on the transformation temperature. The conclusions of the proposed theory quantitatively correspond to the experimental data for phase transformations of low-carbon steels. Запропонована модель базується на використанні принципу детальної рівноваги, яка виникає при фазових переходах кристалічної решітки. Теорія доповнює теорію фазових переходів Ландау в кристалічних середовищах і теорію кристалізації речовини Колмогорова і Аврамі. У запропонованій теорії мартенситні перетворення описуються рівняннями індукованих переходів між двома енергетичними рівнями, які відповідають кількості частинок вихідної фази з низькою енергією (аустеніт) і кількості частинок трансформованої фази з більшою енергією (мартенсит). Джерелом перетворень є фонони, кількість яких пов’язана з індукованими переходами частинок між енергетичними рівнями і залежить від температури перетворення. Висновки кількісно відповідають експериментальним даним для перетворень низьковуглецевих сталей.